PELATIHAN MENYUSUN PANDUAN BELAJAR BAGI ANAK USIA DINI SELAMA BELAJAR DARI RUMAH - Beata Palmin; Maria N. Hadiah Sustik; Aprilia V. Edfra; Agustina S. Jaya (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
Learning from Home (LFH) is one of the policies that must be taken to prevent the expansion of the COVID-19 pandemic. The application of LFH is certainly a challenge for both students and teachers. The challenges of implementing LFH for early childhood experienced by teachers are very complex. The most basic challenge is the lack of understanding of teachers in making learning designs that are easy for parents and children to understand during LHF, and still accommodate learning outcomes in accordance with the school curriculum. A similar problem is experienced by teachers at the Santa Juliana Playgroup. This activity aims to improve the pedagogic abilities of Santa Juliana Early Childhood Education Teachers in planning play activities for children while LFH and make it easier for teachers to collect developmental assessment data. This guide contains a lesson plan format that is more practical and easier for parents to understand, as well as a form of assessment that can be carried out by parents on various activities carried out by children during LFH